In vivo studies on osteoinduction: A systematic review on animal models, implant site, and type and postimplantation investigation. Issue 9 (23rd April 2020) - Veronesi, Francesca; Maglio, Melania; Brogini, Silvia; Fini, Milena
Abstract: Musculoskeletal diseases involving loss of tissue usually require management with bone grafts, among which autografts are still the gold standard. To overcome autograft disadvantages, the development of new scaffolds is constantly increasing, as well as the number of in vivo studies evaluating their osteoinductivity in ectopic sites. The aim of the present systematic review is to evaluate the last 10 years of osteoinduction in vivo studies. The review is focused on: (a) which type of animal model is most suitable for osteoinduction evaluation; (b) what are the most used types of scaffolds; (c) what kind of post‐explant evaluation is most used. Through three websites (www.pubmed.com, www.webofknowledge.com and www.embase.com ), 77 in vivo studies were included. Fifty‐eight studies were conducted in small animal models (rodents) and 19 in animals of medium or large size (rabbits, dogs, goats, sheep, and minipigs). Despite the difficulty in establishing the most suitable animal model for osteoinductivity studies, small animals (in particular mice) are the most utilized. Intramuscular implantation is more frequent than subcutis, especially in large animals, and synthetic scaffolds (especially CaP ceramics) are preferred than natural ones, also in combination with cells and growth factors. Paraffin histology and histomorphometric evaluations are usually employed for postimplantation analyses.